Characterization of Bordetella bronchiseptica associated with atrophic rhinitis outbreak in pigs
The causes of mortality among pigs and piglets suffering from chronic respiratory disease with curvature of turbinate bone in an organized piggery in Meghalaya were investigated. Out of 50 pigs maintained at the farm. 24 (48.0%